Can acupuncture increase microcirculation in peripheral artery disease and diabetic foot syndrome? – a pilot study - Valentini, Jan; Sigl, Martin; Dunckel, Cornelia; Krisam, Johannes; Amendt, Klaus; Greten, Henry Johannes (Frontiers in Medicine, 2024)
Globally, diabetes mellitus (DM) and peripheral artery disease (PAD) have an increasing incidence and a high prevalence and are both associated with high morbidity and complication rates, e.g. as chronic non-healing peripheral ulcers. Impaired macro-and microcirculation and peripheral neuropathy lead to an increased risk of foot ulcers and infections. These complications are difficult to treat, have a high risk of becoming chronic and often lead to lower limb amputation. The aim of this planned study was to investigate the potential effects of acupuncture on improving microcirculation in patients with Diabetic Foot Syndrome (DFS) and PAD.In 18 patients with chronic non-healing peripheral ulcers and diagnosed DM or PAD, data on 8 microcirculatory parameters were collected simultaneously on intact skin close to the wound margin.Microcirculation was assessed using an O2C device combining laser Doppler shift and white light spectroscopy (LEA Medizintechnik GmbH, Giessen, Germany). Unilateral and bilateral acupuncture was performed on the connecting line between acupuncture points Stomach 14 and Stomach 15.After unilateral acupuncture (ipsilateral to the wound side), a statistically significant improvement in 7 out of 8 microcirculatory parameters was demonstrated compared to baseline measurements before acupuncture. After bilateral acupuncture, there was an additional improvement and statistical significance in all parameters in both DFS and PAD patients.These results show an improvement in the microcirculation and peripheral blood flow at the edges of the wound. As impaired micro-and macrocirculation is considered to be a critical prognostic factor for the healing of a peripheral lesion, the intervention could have a positive impact on the healing of (chronic) peripheral wounds.